Governance Readiness for Decentralised Waste Management: A Five-Pillar Assessment of the Integrated Waste Processing Unit (IWPU) Model in Kabupaten Bogor, Indonesia - Arraisya Rohasyah; Valid Hasyimi (Siber Journal of Advanced Multidisciplinary, 2026)
Decentralised waste management is a critical upstream complement to Indonesia's centralised Waste-to-Energy agenda under Presidential Regulation No. 109/2025. Yet the operational failure rate of existing community-based waste facilities exceeds 40%, indicating that governance conditions are the primary determinant of sustainability. This study assesses the governance readiness of the Integrated Waste Processing Unit (IWPU) model in Kabupaten Bogor using a five-pillar framework adapted from the Integrated Sustainable Waste Management (ISWM) approach. The five pillars assessed are: Social-Cultural, Financing, Technical Operations, Institutional, and Regulatory. Drawing on primary data from expert forums and a national workshop (March 2026), each pillar is evaluated as Ready, Partially Ready, or Not Ready. All five pillars are rated Partially Ready, indicating that foundational conditions exist but critical operational mechanisms have not yet been established. Integrated with financial feasibility analysis (NPV IDR 7.58 billion, IRR 17.9%), findings position Kabupaten Bogor in a Conditional Investment position. Tipping fee formalisation and inter-agency waste supply contracting are identified as the highest-priority pre-investment actions.